Writing Toward and With: Ethological Poetics and Nonhuman Lives. (2nd January 2020) - Cooke, Stuart
Abstract: In this essay, the author argues that the appreciation of nonhuman poetic forms, or an "ethological poetics, " is a necessary but neglected mode of ecological relation, and is especially important in the Anthropocene. Motivated by his own creative practice—in particular, the composition of Lyre, a book of poems about different animals, plants, and landforms—he considers important examples of ethologically attentive poetics before outlining how his compositional method attempts to incorporate insights from the environmental humanities and animal studies. Rather than insisting on their essential difference from human worlds, the author argues for an attentive, ethical, and imaginative engagement with nonhuman lives, through which surprising and unusual forms of poetry might emerge.